A1.55 Development of antibodies specific for carbamylated protein precedes disease onset in MICE with collagen-induced arthritis. (31st January 2014) - Verheul, M K; Stoop, J N; Liu, B S; Shi, J; Jansen, D T S L; Hegen, M; Huizinga, T W J; Trouw, L A; Toes, R E M
Abstract : Background: Antibodies against citrullinated proteins are a characteristic of rheumatoid arthritis (RA). Recently, we demonstrated that autoantibodies recognizing homocitrulline containing proteins are present in sera of RA patients and predict joint damage (1). Because homocitrulline is post-translationally formed by a process called carbamylation, we named these novel auto-antibodies anti-Carbamylated Protein antibodies (anti-CarP antibodies). As no information is present on the molecular mechanisms underlying the break of tolerance and hence the induction of anti-CarP-responses, we analysed their appearance in the mouse collagen-induced arthritis (CIA) model. Methods: CIA was induced in mice by immunisation with type II collagen (CII) in complete Freund's adjuvant (CFA). Arthritis severity was monitored by clinical scoring and anti-CarP levels were determined by ELISA. The specificity of the ELISA was validated using inhibition and immunoblotting assays. Results: Anti-CarP antibodies were not detected in naïve, non-immunised mice. However they were readily detectable in mice injected with CII and CFA demonstrating arthritic scores. The ELISA results of the specificity of the antibodies for carbamylated proteins were confirmed by inhibition assays and immunoblotting. No correlation between anti-CarP antibody levels and disease severity was observed. Injection of CFA could also cause the development of anti-Carp antibodies, indicating that arthritis is not required for the emergence of anti-CarP antibodies. However, in mice with arthritic disease, the anti-CarP response was stronger and developed more rapidly. The onset of clinical symptoms of CIA was preceded by an increase of anti-CarP IgG2a levels in the serum. Conclusion: Anti-CarP antibodies can be detected before disease onset in mice with CIA, but are not required for disease induction. Our data indicate that induction of inflammation by e.g. CFA can lead to a break of B-cell tolerance to carbamylated proteins and the emergence of anti-CarP-antibodies. Disclosure: This project is supported by Pfizer Inc. as part of the IMI BTCure program. L. A. T. receives a fellowship from Janssen Biologics BV (Johnson & Johnson). M. H. is a Pfizer Inc. employee. Reference: Shi J, et al. Autoantibodies recognizing carbamylated proteins are present in sera of patients with rheumatoid arthritis and predict joint damage. Proc. Natl. Acad. Sci. U. S. A 2011;108:17372-7.